Ethnopharmacology as a complementary therapy in primary care: an integrative review (Research, Society and Development, 2021)
Ethnopharmacology deals with popular knowledge concerning traditional systems of medicine; it consists of information acquired throughout life by the population using medicinal flora as pharmacological study. The aim is to analyze the scientific evidence of health professionals' knowledge of the use of ethnopharmacology as a complementary therapy in primary care. An integrative literature review was conducted using the online search platforms Us National Library of Medicine (PUBMED) and Virtual Health Library (VHL) in the databases LILACS, MEDLINE and BDENF. To construct the research question of the integrative review, the Pico strategy was used, essential for increasing the specificity and conceptual clarity of the situation to be studied, providing results of greater quality and uniqueness.  Articles indexed in national and international journals were selected, provided in full, and studies found in the last 5 years in Portuguese, English and Spanish. The results suggest that although phytotherapy is a beneficial practice for many, there are still factors that act as barriers to the consolidation of this therapy within health services. Therefore, it becomes extremely important to mobilize strategies that can pave the way for the effective implementation of ethnopharmacological practices as an integral part of the users' health management.